Design and Characterization of a Miniaturized Antenna Based on Palisade-Shaped Metasurface - Ximing Li; Jingjing Yang; Zhigang Chen; Pengshan Ren; Ming Huang (International Journal of Antennas and Propagation)
A palisade-shaped metasurface (PSMS) is presented to miniaturize the micropatch antenna. With the aid of the metasurface, a footprint miniaturization is obtained, and the dual resonant modes are produced simultaneously. Furthermore, through analyzing the dispersion curve of the metasurface to optimize the structure, the proposed antenna achieves a compact structure with a maximum size of 0.38λ02; a low profile of 0.08λ0 (where λ0 is the free-space wavelength at 5.0 GHz) exhibits a 19.6% impedance bandwidth (S11<−10dB) and an average gain of 6.76 dBi across the bandwidth.